Sedimentology and geochemistry of Middle–Upper Permian in northwestern Turpan–Hami Basin, China: Implication for depositional environments and petroleum geology. Issue 4 (July 2018) - Song, Jian; Bao, Zhidong; Zhao, Xingmin; Gao, Yinshan; Song, Xinmin; Zhu, Yanzhen; Deng, Jian; Liu, Wei; Wang, Zecheng; Ming, Chengdong; Meng, Qingkui; Zhang, Li; et al.
Studies have found that the Permian is another important stratum for petroleum exploration except the Jurassic coal measures within Turpan–Hami Basin recently. However, the knowledge of the depositional environments and its petroleum geological significances during the Middle–Late Permian is still limited. Based on the analysis about the sedimentological features of the outcrop and the geochemical characteristics of mudstones from the Middle Permian Taerlang Formation and Upper Permian Quanzijie Formation in the Taoshuyuanzi profile, northwest Turpan–Hami Basin, this paper makes a detailed discussion on the Middle–Late Permian paleoenvironment and its petroleum geological significances. The Middle–Upper Permian delta–lacustrine depositional system was characterized by complex vertical lithofacies assemblages, which were primarily influenced by tectonism and frequent lake-level variations in this area. The Taerlang Formation showed a significant lake transgression trend, whereas the regressive trend of the Quanzijie Formation was relatively weaker. The provenance of Taerlang and Quanzijie Formations was derived from the rift shoulder (Bogda Mountain area now) to the north and might be composed of a mixture of andesite and felsic volcanic source rocks. The Lower Taerlang Formation was deposited in a relatively hot–dry climate, whereas the Upper Taerlang and Quanzijie Formations were deposited in a relatively humid climate. During the Middle–Late Permian, this area belonged to an overall semi-saline water depositional environment. The paleosalinity values showed stepwise decreases from the Lower Taerlang Formation to the Upper Quanzijie Formation, which was influenced by the changes of paleoclimate in this region. During the Middle–Late Permian, the study area was in an overall anoxic depositional environment. The paleoenvironment with humid climate, lower paleosalinity, anoxic condition, and semi-deep to deep water during the deposition of the Upper Taerlang Formation was suitable for the accumulation of mudstones with higher TOC values.